Konzeption modellbasierter Benutzungsschnittstellen für verteilte Selbstbedienungssysteme - Yigitbas, Enes; Gerth, Christian; Sauer, Stefan (Informatik 2013, 43. Jahrestagung der Gesellschaft für Informatik e.V. (GI), Informatik angepasst an Mensch, Organisation und Umwelt, 16.-20. September 2013, Koblenz, Deutschland)

A Taxonomy-Based Approach towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard (Distributed, Ambient, and Pervasive Interactions)

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten (Design, User Experience, and Usability. Design Philosophy, Methods, and Tools)

Do You Speak Usability? - Aktueller Stand des Glossars und des Curriculums für den Certified Professional for Usability and User Experience (CPUX) der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter (Jahresband Usability Professionals)

Zero Overhead Runtime Monitoring - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the 11th International Conference on Software Engineering and Formal Methods (SEFM))
Runtime monitoring aims at ensuring program safety by monitoring the program's behaviour during execution and taking appropriate action before a program violates some property.Runtime monitoring is in particular important when an exhaustive formal verification fails. While the approach allows for a safe execution of programs, it may impose a significant runtime overhead.In this paper, we propose a novel technique combining verification and monitoring which incurs no overhead during runtime at all. The technique proceeds by using the inconclusive result of a verification run as the basis for transforming the program into one where all potential points of failure are replaced by HALT statements. The new program is safe by construction, behaviourally equivalent to the original program (except for unsafe behaviour),and has the same performance characteristics.

Which Flows Are Hiding Behind My Wildcard Rule? Adding Packet Sampling to OpenFlow - Wette, Philip; Karl, Holger (Proceedings of the ACM SIGCOMM '13)
In OpenFlow [1], multiple switches share the same control plane which is centralized atwhat is called the OpenFlow controller. A switch only consists of a forwarding plane. Rules for forwarding individual packets (called ow entries in OpenFlow) are pushed from the controller to the switches. In a network with a high arrival rate of new ows, such as in a data center, the control trac between the switch and controller can become very high. As a consequence, routing of new ows will be slow. One way to reduce control trac is to use wildcarded ow entries. Wildcard ow entries can be used to create default routes in the network. However, since switches do not keep track of ows covered by a wildcard ow entry, the controller no longer has knowledge about individual ows. To nd out about these individual ows we propose an extension to the current OpenFlow standard to enable packet sampling of wildcard ow entries.

Verteilte Erstellung und Aktualisierung von Schlüsselservern in identitätsbasierten Verschlüsselungssystemen - Tezer, Alina

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (Theory of Computing Systems)
An elementary h-route ow, for an integer h 1, is a set of h edge- disjoint paths between a source and a sink, each path carrying a unit of ow, and an h-route ow is a non-negative linear combination of elementary h-routeows. An h-route cut is a set of edges whose removal decreases the maximum h-route ow between a given source-sink pair (or between every source-sink pair in the multicommodity setting) to zero. The main result of this paper is an approximate duality theorem for multicommodity h-route cuts and ows, for h 3: The size of a minimum h-route cut is at least f=h and at most O(log4 k f) where f is the size of the maximum h-routeow and k is the number of commodities. The main step towards the proof of this duality is the design and analysis of a polynomial-time approximation algorithm for the minimum h-route cut problem for h = 3 that has an approximation ratio of O(log4 k). Previously, polylogarithmic approximation was known only for h-route cuts for h 2. A key ingredient of our algorithm is a novel rounding technique that we call multilevel ball-growing. Though the proof of the duality relies on this algorithm, it is not a straightforward corollary of it as in the case of classical multicommodity ows and cuts. Similar results are shown also for the sparsest multiroute cut problem.

Token Dissemination in Geometric Dynamic Networks - Abshoff, Sebastian; Benter, Markus; Cord-Landwehr, Andreas; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013, Sophia Antipolis, France, September 5-6, 2013, Revised Selected Papers)
We consider the k-token dissemination problem, where k initially arbitrarily distributed tokens have to be disseminated to all nodes in a dynamic network (as introduced by Kuhn et al., STOC 2010). In contrast to general dynamic networks, our dynamic networks are unit disk graphs, i.e., nodes are embedded into the Euclidean plane and two nodes are connected if and only if their distance is at most R. Our worst-case adversary is allowed to move the nodes on the plane, but the maximum velocity v_max of each node is limited and the graph must be connected in each round. For this model, we provide almost tight lower and upper bounds for k-token dissemination if nodes are restricted to send only one token per round. It turns out that the maximum velocity v_max is a meaningful parameter to characterize dynamics in our model.

Three-Valued Abstraction and Heuristic-Guided Refinement for Verifying Concurrent Systems - Timm, Nils
Software systems are playing an increasing role in our everyday life, and as the amount of software applications grows, so does their complexity and the relevance of their computations. Software components can be found in many systems that are charged with safety-critical tasks, such as control systems for aviation or power plants. Hence, software verification techniques that are capable of proving the absence of critical errors are becoming more and more important in the field software engineering. A well-established approach to software verification is model checking. Applying this technique involves an exhaustive exploration of a state space model corresponding to the system under consideration. The major challenge in model checking is the so-called state explosion problem: The state space of a software system grows exponentially with its size. Thus, the straightforward modelling of real-life systems practically impossible. A common approach to this problem is the application of abstraction techniques, which reduce the original state space by mapping it on a significantly smaller abstract one. Abstraction inherently involves a loss of information, and thus, the resulting abstract model may be too imprecise for a definite result in verification. Therefore, abstraction is typically combined with abstraction refinement: An initially very coarse abstract model is iteratively refined, i.e. enriched with new details about the original system, until a level of abstraction is reached that is precise enough for a definite outcome. Abstraction refinement-based model checking is fully automatable and it is considered as one of the most promising approaches to the state explosion problem in verification. However, it is still faced with a number of challenges. There exist several types of abstraction techniques and not every type is equally well-suited for all kinds of systems and verification tasks. Moreover, the selection of adequate refinement steps is nontrivial and typically the most crucial part of the overall approach: Unfavourable refinement decisions can compromise the state space-reducing effect of abstraction, and as a consequence, can easily lead to the failure of verification. It is, however, hard to predict which refinement steps will eventually be expedient for verification – and which not.

Symbiotic Coupling of P2P and Cloud Systems: The Wikipedia Case - Graffi, Kalman; Bremer, Lars (Proceedings of the International Conference on Communications (ICC'13))
Cloud computing offers high availability, dynamic scalability, and elasticity requiring only very little administration. However, this service comes with financial costs. Peer-to-peer systems, in contrast, operate at very low costs but cannot match the quality of service of the cloud. This paper focuses on the case study of Wikipedia and presents an approach to reduce the operational costs of hosting similar websites in the cloud by using a practical peer-to-peer approach. The visitors of the site are joining a Chord overlay, which acts as first cache for article lookups. Simulation results show, that up to 72% of the article lookups in Wikipedia could be answered by other visitors instead of using the cloud.

Service Matching under Consideration of Explicitly Specified Service Variants - Platenius, Marie Christin; von Detten, Markus; Gerth, Christian; Schäfer, Wilhelm; Engels, Gregor (IEEE 20th International Conference on Web Services (ICWS 2013))
One of the main ideas of Service-Oriented Computing (SOC) is the delivery of flexibly composable services provided on world-wide markets. For a successful service discovery,service requests have to be matched with the available service offers. However, in a situation in which no service that completely matches the request can be discovered, the customer may tolerate slight discrepancies between request and offer. Some existing fuzzy matching approaches are able to detectsuch service variants, but they do not allow to explicitly specify which parts of a request are not mandatory. In this paper, we improve an existing service matching approach based onVisual Contracts leveraging our preliminary work of design pattern detection. Thereby, we support explicit specifications of service variants and realize gradual matching results that can be ranked in order to discover the service offer that matches a customer’s request best.

Semi-Automated Software Composition Through Generated Components - Mohr, Felix; Kleine Büning, Hans (Proceedings of the 15th International Conference on Information Integration and Web-based Applications & Services (iiWAS))
Software composition has been studied as a subject of state based planning for decades. Existing composition approaches that are efficient enough to be used in practice are limited to sequential arrangements of software components. This restriction dramatically reduces the number of composition problems that can be solved. However, there are many composition problems that could be solved by existing approaches if they had a possibility to combine components in very simple non-sequential ways. To this end, we present an approach that arranges not only basic components but also composite components. Composite components enhance the structure of the composition by conditional control flows. Through algorithms that are written by experts, composite components are automatically generated before the composition process starts. Therefore, our approach is not a substitute for existing composition algorithms but complements them with a preprocessing step. We verified the validity of our approach through implementation of the presented algorithms.

Seitenkanalresistenz paarungsbasierter Kryptographie - Otte, Oliver

Security Proofs for Pairing-Based Cryptography in the Generic Group Model - Bobolz, Jan

Securing Critical Unattended Systems with Identity Based Cryptography - A Case Study - Blömer, Johannes; Günther, Peter; Krummel, Volker (Proceedings of the 5th International Conference on Mathematical Aspects of Computer and Information Sciences (MACIS))
Unattended systems are key ingredients of various critical infrastruc-tures like networks of self service terminals or automated teller machines.For cost and efficiency reasons they should mostly run autonomously.Unattended systems are attractive and lucrative targets for various kindsof attacks, including attacks on the integrity of their components and thecommunication between components. In this paper, we propose a gen-eral cryptographic framework to protect unattended systems. We alsodemonstrate that instantiating the framework with techniques from iden-tity based cryptography is particularly well-suited to efficiently secureunattended systems.

Routing in heterogenen OpenFlow Netzwerken - Wallaschek, Felix

Ressource-Optimized Deployment of Multi-Tier Applications - The Data Rate-Constrained Case - Robbert, Christoph

Reengineering of Component-Based Software Systems in the Presence of Design Deficiencies - von Detten, Markus
The maintenance of component-based software systems requires up-to-date models of their concrete architecture, i.e. the architecture that is realised in the source code. These models help in systematically planning, analysing and executing typical reengineering activities. Often no or only outdated architectural models of such systems exist. Therefore, various reverse engineering methods have been developed which try to recover a system's components, subsystems and connectors. However, these reverse engineering methods are severely impacted by design deciencies in the system's code base, especially violations of the component encapsulation. As long as design deciencies are not considered in the reverse engineering process, they reduce the quality of the recovered component structures. Despite this impact of design deciencies, no existing architecture reconstruction approach explicitly integrates a systematic deciency detection and removal into the recovery process. Therefore, I have developed Archimetrix. Archimetrix is a tool-supported architecture reconstruction process. It enhances a clustering-based architecture recovery approach with an extensible, pattern-based deciency detection. After the detection of deciencies, Archimetrix supports the software architect in removing the de ciencies and provides the means to preview the architectural consequences of such a removal. I also provide a process to identify and formalise additional deciencies. I validated the approach on three case studies which show that Archimetrix is able to identify relevant deciencies and that the removal of these deciencies leads to an increased quality of the recovered architectures, i.e. they are closer to the corresponding conceptual architectures.

Reducing Nondeterminism in Automated Service Composition - Mohr, Felix; Lettmann, Theodor; Kleine Büning, Hans (Proceedings of the 6th International Conference on Service Oriented Computing and Applications (SOCA))
Automated service composition has been studied as a subject of state based planning for a decade. A great deal of service composition tasks can only be solved if concrete output values of the services are considered in the composition process. However, the fact that those values are not known before runtime leads to nondeterministic planning problems, which have proven to be notoriously difficult in practical automated service composition applications. Even though this problem is frequently recognized, it has still received remarkably few attention and remains unsolved.This paper shows how nondeterminism in automated service composition can be reduced. We introduce context rules as a means to derive semantic knowledge from output values of services. These rules enable us to replace nondeterministic composition operations by less nondeterministic or even completely deterministic ones. We show the validity of our solutions not only theoretically but also have evaluated them practically through implementation.